A Simplified Framework for Seismic Fragility Assessment of Reinforced Concrete Columns under Different Failure Patterns. Issue 9 (4th July 2022) - Ning, Chao-Lie; Wang, Li-Ping; Cheng, Yin; Yu, Xiao-Hui
ABSTRACT: A simplified framework is proposed in this study to assess the seismic fragility curves of reinforced concrete (RC) columns under different failure patterns in a unified manner. Within this framework, RC columns are simulated by an equivalent single-degree-of-freedom system, where a quasi-static experimental database is compiled to calibrate the seismic demand model and identify the limit state capacity. By comparing the seismic demand model with the limit state capacity, the seismic fragility curves of RC columns under different failure patterns are generated accordingly. Finally, empirical equations are proposed to predict the seismic fragility parameters for engineering applications.